Soil Characteristics and Hydromorphological Patterns Control Denitrification at the Floodplain Scale - Kaden, Ute Susanne; Fuchs, Elmar; Geyer, Sophie; Hein, Thomas; Horchler, Peter; Rupp, Holger; Scholz, Mathias; Schulz-Zunkel, Christiane; Weigelhofer, Gabriele (Frontiers in Earth Science, 2021)
Nitrate pollution in aquatic ecosystems is still a major problem in Germany. There is a great potential to permanently remove nitrate from aquatic systems through denitrification as a relevant ecosystem function. However, the controlling factors and the dimension of the denitrification potential are still not fully understood due to the high complexity of the process. This study presents the combined assessment of potential soil denitrification rates, physical and chemical soil parameters, and hydrological parameters from six floodplains of four large German rivers, namely the Rhine, the Elbe, the Weser, and the Main. Based on multivariate statistics, results show that the denitrification potential of soil was almost solely controlled by soil pH. The lab assays showed mean soil denitrification potentials of 6.4–11.4 mg N m−2 h−1 (pH < 7) and 23.0–30.5 mg N m−2 h−1 (pH > 7). We contend that when upscaling these estimates to annual rates of potential denitrification, the duration of average inundation should be incorporated, as this accounts for water saturation and nutrient supply − the major controlling variables for denitrification. Results provide evidence that the denitrification potential can only be fully exploited in frequently inundated floodplains. Thus, despite favorable soil conditions for denitrification, floodplains that have suffered from anthropogenic impacts, lose their importance in nitrate removal for the river system. We conclude that pH and lateral hydrological connectivity are likely to be key factors that should be considered when estimating denitrification as an ecosystem function.